Anarchy and its Breakdown - Hirshleifer, Jack (Journal of Political Economy, 1995)
Anarchy, defined as a system in which participants can seize and defend resources without regulation from above, is not chaos but rather a spontaneous order. However, anarchy is fragile and may dissolve either into formless "amorphy" or into a more organized system such as hierarchy. Under anarchy, each contestant balances between productive exploitation of the current resource base and fighting to acquire or defend resources. Anarchy is sustainable only when there are strongly diminishing returns to fighting effort (the "decisiveness parameter" is sufficiently low) and incomes exceed the viability minimum. These considerations explain many features of animal and human conflict.